Investigating the effect of yoga-based educational interventions on the volume and composition of breast milk in premature infant’s mothers admitted to neonatal intensive care unit: A randomized controlled trial - Fatemeh Karimi; Parvin Aziznejadroshan; Zahra Akbarian Rad; Hossein-Ali Nikbakht; Durdi Qujeq (Journal of Education and Health Promotion)
Background: This study examined the effects of yoga-based educational interventions on the volume and composition of breast milk in premature infants’ mothers admitted to the neonatal intensive care unit (NICU). Materials and Methods: A randomized controlled trial was conducted on 78 primiparous mothers whose premature infants were less than 34 weeks and were hospitalized in the NICU of Ayatollah Rouhani Hospital from February 2021 to November 2022. Mothers were assigned to a control group and an experimental group, that is, yoga, using the block randomization method. Mothers in the experimental group performed yoga for 30 minutes under the supervision of a yoga therapist every morning for six consecutive days. The volume of the mother’s milk was measured using an electric pump, while its composition was assessed using a spectrophotometer according to the instructions of the Pars Azmoun Standard Kit. Results: The results of the analysis on the remaining 76 samples showed a difference in the means of the volume of breast milk after the intervention with 11.39 and 33.84 ml for the control and yoga group, respectively.there was a significant difference between the amount of breast milk in the control and yoga groups (P < 0.001). Also, the average difference in the amount of breast milk compounds was not significantly different in any of the cases. Conclusions: The yoga technique is effective in increasing the volume of breast milk in mothers with premature infants. Therefore, it is recommended to increase the volume of breast milk in the NICU.